Elucidation of the origin of 'agriocrithon' based on domestication genes questions the hypothesis that Tibet is one of the centers of barley domestication. (6th April 2018) - Pourkheirandish, Mohammad; Kanamori, Hiroyuki; Wu, Jianzhong; Sakuma, Shun; Blattner, Frank R.; Komatsuda, Takao
SUMMARY: Wild barley forms a two‐rowed spike with a brittle rachis whereas domesticated barley has two‐ or six‐rowed spikes with a tough rachis. Like domesticated barley, ' agriocrithon ' forms a six‐rowed spike; however, the spike is brittle as in wild barley, which makes the origin of agriocrithon obscure. Haplotype analysis of the Six‐rowed spike 1 ( vrs1 ) and Non‐brittle rachis 1 ( btr1 ) and 2 ( btr2 ) genes was conducted to infer the origin of agriocrithon barley. Some agriocrithon barley accessions ( eu‐agriocrithon ) carried Btr1 and Btr2 haplotypes that are not found in any cultivars, implying that they are directly derived from wild barley through a mutation at the vrs1 locus. Other agriocrithon barley accessions ( pseudo‐agriocrithon ) carried Btr1 or Btr2 from cultivated barley, thus implying that they originated from hybridization between six‐rowed landraces carrying btr1Btr2 and Btr1btr2 genotypes followed by recombination to produce Btr1Btr2 . All materials we collected from Tibet belong to pseudo‐agriocrithon and thus do not support the Tibetan Plateau as being a center of barley domestication. Tracing the evolutionary history of these allelic variants revealed that eu‐agriocrithon represents six‐rowed barley lineages that were selected by early farmers, once in south‐eastern Turkmenistan ( vrs1.a1 ) and again in the eastern part of Uzbekistan ( vrs1.a4 ). Significance Statement: We show that two of the ancestors of today's six‐rowed barley emerged in Central Asia during the cultivation of wild relatives by early farmers, once close to Turkmenistan and a second time in the approximate area of Uzbekistan. Our data suggest that Tibetan barley was the result of genetic recombination but does not support the Tibetan Plateau as being a center of barley domestication.